2017
DOI: 10.1038/s41598-017-12168-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the inhibition effect and mechanism of myricetin to Suilysin by molecular modeling

Abstract: In the present study, the inhibitory effect and mechanism of myricetin, a natural flavonoid compound, in relation to Suilysin (SLY) were investigated through molecular dynamics simulations, mutational analysis and fluorescence-quenching assays. Myricetin is a potential inhibitor that does not exhibit antimicrobial activity but has been shown to inhibit SLY cytotoxicity. Molecular dynamics simulations and mutational analysis revealed that myricetin binds directly to SLY in the gap between domains 2 and 3, an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…In vitro , this study finds that fisetin efficiently inhibits the hemolytic activity of suilysin ( Figure 1C ), and that it has little antibacterial activity against SC19 at the concentrations of 32 μg/ml ( Figure 2A ). The result of our study is consistent with that of the experiment by Niu et al (2017) who reported that myricetin inhibited suilysin cytotoxicity without exhibiting antimicrobial activity. Meanwhile, Li et al (2017) reported that another flavonoid morin hydrate protects mice from SS2 infection by inhibiting the hemolytic activity of suilysin.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In vitro , this study finds that fisetin efficiently inhibits the hemolytic activity of suilysin ( Figure 1C ), and that it has little antibacterial activity against SC19 at the concentrations of 32 μg/ml ( Figure 2A ). The result of our study is consistent with that of the experiment by Niu et al (2017) who reported that myricetin inhibited suilysin cytotoxicity without exhibiting antimicrobial activity. Meanwhile, Li et al (2017) reported that another flavonoid morin hydrate protects mice from SS2 infection by inhibiting the hemolytic activity of suilysin.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found that the hemolytic activity of supernatant incubated with fisetin was inhibited ( Figure 1D ), and that there was no significant difference in suilysin expression level of SC19 with 32 μg/ml of fisetin ( Figure 2B ). Taken together, fisetin inhibits the hemolytic activity of SC19 as described by Li et al (2017) and Niu et al (2017) .…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Qiu et al demonstrated that baicalin could reduce the activity of α-hemolysin of Staphylococcus aureus ( S. aureus ) through binding to α-toxin and hindering the formation of functional heptamer, which resulted in the decrease of pathogenicity of S. aureus to mice [ 39 ]. Myricetin, a natural flavonoid compound, has been reported to be a candidate for the treatment of Streptococcus suis by abolishing the activity of suilysin via inhibiting oligomer formation [ 40 ]. Lu et al found that betulin attenuated the virulence of Listeria monocytogenes in a mice infection model by suppressing the oligomerization process of listeriolysin O (LLO) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%